FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI WILAYAH BOGOR - Maria Ade Kristina; Rian Sumarta (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to determine the factors that influence the control of personal taxpayers registered at Bogor. These factors are tax authorities services, tax penalty, level of understanding, tax awareness, tax dissemination, perceptions of tax effectiveness, and taxpayer trust. This research was conducted in 2022 with the object of research for taxpayers who were registered at Bogor. Primary data test method by means of a questionnaire. The sampling technique used purposive sampling with the number of samples in this study were 103 respondents. The data analysis method used in this research is validity test, reliability test, classical assumption test, correlation coefficient analysis, determination coefficient analysis (adj R²), overall significance test (F test), and individual parameter significance test (t test). The results showed that tax services, tax penalty, tax awareness, tax socialization, and taxpayer trust had no effect on taxation. However level of understanding and perception of tax effectiveness had effect on taxation.